Peran Sistem Operasi Seluler dalam Meningkatkan Efisiensi Energi dan Keamanan Mobile Banking untuk Perekonomian Berkelanjutan - Rakhmadi Rahman; Retno Helviani; Nur Afiat (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In the digital era, mobile operating systems (OS) play a pivotal role beyond mere application execution platforms. They are essential for optimizing energy efficiency and enhancing security, particularly in the realm of mobile banking. This paper explores the critical role of mobile OS in supporting sustainable economic growth through efficient energy use and robust security measures in mobile banking transactions. The focus is on how these OS advancements contribute to a secure and environmentally responsible digital economy. Key aspects covered include energy optimization strategies, security enhancements such as data encryption and multi-factor authentication, and the integration of these technologies into mobile banking applications. By addressing these challenges, mobile OS not only ensures sustainable economic development but also fosters financial inclusivity and security in an increasingly digital world.